Price Sensitivity and Ski Pass Purchases: A Comparison Across Slovenian and International Resorts - Vukovič, Goran; Raspor, Andrej; Toroš, Niki (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Skiing has always been popular among Slovenians. However, in recent years, we have been experiencing increasingly greener winters, which in turn has made the price of ski passes more expensive. As a result, we wanted to determine whether price increases at Slovenian ski resorts are lagging behind those of competitors in Italy and Austria, and how gender, age, and income affect the price elasticity of ski users. Using a historical method, we analysed data on the evolution of ski pass prices and found that ski passes in Slovenia are no more expensive than in Italy and Austria. In addition, we conducted an online survey with 536 participants. We found that retail prices have increased by 60% since 2006. The analysis showed that Slovenian skiers are not willing to give up skiing, even if prices were to increase further.